An interactive approach to enhancing early word learning from research to best practice - Gogate, Lakshmi, 1962- (Cambridge Scholars Publishing, 2022)
A wealth of research on child language has unearthed many novel strategies that parents and interventionists can utilise to enhance word learning prior to infants producing their first words. These developmentally-appropriate strategies are published in scientific journals, however, rendering them largely inaccessible to parents and non-research professionals. This volume presents research findings and practices in an accessible, user-friendly manner. A sizeable percentage of children entering first grade each year show vocabulary delays. However, best practices for enhancing vocabulary focus.